Coralyne has a preference for intercalation between TA.T triples in intramolecular DNA triple helices. - Moraru-Allen, A; Cassidy, S; Asensio Alvarez, J; Fox, K; Brown, T; Lane, A (1997)
Intercalating ligands may improve both the stability and sequence specificity of triple helices. Numerous intercalating drugs have been described, including coralyne, which preferentially binds triple helices, though its sequence specificity has been reported to be low [Lee,J.S., Latimer,L.J.P. and Hampel,K.J. (1993) Biochemistry , 32, 5591-5597]. In order to analyse the sequence preferences of coralyne we have used a combination of DNase I footprinting, UV melting, UV-visible spectrophotometry, circular dichroism and NMR spectroscopy to examine defined intermolecular triplexes and intramolecular triplexes linked either by hexaethylene glycol chains or by octandiol chains. DNase I footprinting demonstrated that coralyne has a moderate preference for triplexes over duplexes, but a substantial preference for TA.T triplets compared with CG. C+triplets. The drug was found to have essentially no effect on the melting temperatures of duplexes of the kind d(A)n.d(T)n or d(GA)n.d(TC)n. In contrast, it increased the T m for triplexes of the kind d(T)nd(A)n.dTn, but had little effect on the stability of d(TC)nd(GA).d(CT)n at either low or high pH. On binding to DNA triplexes, there is a large change in the absorption spectrum of coralyne and also a substantial fluorescence quenching that can be attributed to intercalation. The changes in the optical spectra have been used for direct titration with DNA. For triplexes d(T)6d(A)6.d(T)6, the Kd at 298 K was 0.5-0.8 microM. In contrast, the affinity for d(TC) nd(GA)n.d(CT)n triplexes was 6- to 10-fold lower and was characterized by smaller changes in the absorption and CD spectra. This indicates a preference for intercalation between TAT triples over CG.C+/TA.T triples. NMR studies confirmed interaction by intercalation. However, a single, secondary binding was observed at high concentrations of ligand to the triplex d(AGAAGA-L-TCTTCT-L-TCTTCT), presumably owing to the relatively low difference in affinity between the TA.T site and the competing, neighbouring sites.